Akuaponik sebagai Pembelajaran Lingkungan Hidup Siswa SMA yang Selaras Misi Sekolah Adiwiyata - Tapilouw, Marisa Christina; Djohan; Sucahyo; Hartadji, Ezer Widhi; Zega, Yakin Teguh (Jurnal SOLMA, 2025)
Background: Community service with aquaponic theme linked with natural environment education. The urgency of this community service’s activity with aquaponic theme were to accomplish Adiwiyata program’s component, which are environmental based school curriculum aspect and participative based school activity. Methods: Community service partners are SMA Negeri 3, SMAK Satya Wacana Salatiga and this activity was done ini October-December 2024. The participants were 23 students from each school. The procedure was included observation; preparation; presentation; implementation; evaluation. Results: The students who participated in this community service activity were enthusiast in aquaponic implementation as a form of environment education. Main hope is students involved actively in maintaining aquaponic system, so that there will be environmental sustainability and fish-plants cultivation. Conclusions: Participants’ response were positive in terms of usefulness activity and alignment with school’s Adiwiyata program. Keywords: Aquaponic; Natural environment; Adiwiyata.